Tafsir Tarbawi: Analisis Bahasa dan Sastra al-Qur’an dalam Surah Luqman - Ibnu Rawandhy N. Hula (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2020)
This study aims to uncover the interpretation of tarbawi>, as one of the features / interpretations approached by the analysis of language and literature. The object of his research was examined from Surah Luqman verses 12 to 19, which generally contain messages and educational values. This type of research is library research, by reading, taking notes, identifying the text content of the Surah Luqman and then analyzing it from three aspects,, 1) language analysis/ lugawi>, 2) literature analysis/ bala>gi> and 3) analysis of educational values/tarbawi>. The results showed that the language content contained in Surah Luqman had depth and diversity of meanings, contained in several words: al-hakim/al-hikmah, al-fis}a>l/al-fit}a>m, al-wa’z|, bunayya, al-wahn/al-d}a’f, al-tus}a’ir, al-marh /al-farh, al-mukhta<l, al-qasd dan al-gad}d}. As for the literary aspect, it contains a number of beauty editors and their meanings, namely: al-tiba>q, s}i>gah al-muba>lagah, zikr al-khas}s{ ba’da al-‘a>mm, al-tams}i>l, al-muqa<balah, al-taqdi>m wa al-ta’khi>r, al-tatayammum, dan al-istia>’rah al-tams|i>liyah, While the value of education consists of: Faith Values, worship values ​​and moral values, which consist of: not shirk, establishing prayer, enjoin the good and forbid the evil, good association, thanks giving, patience, filial piety, not exulting overmuch, arrogant and not self-conceited boaster.